From Catalytic Test Reaction to Modern Chemical Descriptors in Zeolite Catalysis Research. Issue 6 (22nd February 2021) - Prodinger, Sebastian; Beato, Pablo; Svelle, Stian
Abstract: For the successful implementation of catalysts in industrial processes, three overall goals are optimized: activity, selectivity, and stability. This review will address the role of chemical descriptors in aiding and guiding the development of optimal zeolite catalyst designs with the above performance criteria in mind. It will focus on both gas‐phase and liquid‐phase catalysis with a special focus on methanol to hydrocarbon, and biomass valorization reactions. By way of preface, the research on constraint and spaciousness indices is discussed. These indices can be considered the original chemical descriptors of catalysis research. Abstract : The relevance of chemical test reactions (e.g., constraint index) used to establish early descriptors for pore size and the impact they had on the development and understanding of zeolite catalysts in modern applications such as methanol to hydrocarbons and biomass transformations are revisited.